2019
DOI: 10.29228/turkishstudies.22563
|View full text |Cite
|
Sign up to set email alerts
|

Sosyal Bi̇lgi̇ler Öğretmen Adaylarinin Di̇ji̇tal Okuryazarlik Kavramina İli̇şki̇n Görüşleri̇

Abstract: gerekenlerin belirlenmesini gerektirmektedir. Sonuçlar ışığında alt problemlere yönelik olarak önerilerde bulunulmuştur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 5 publications
0
5
0
1
Order By: Relevance
“…With the penetration of technology into all areas of life, and in particular educational institutions, the necessity for students to use technology effectively and consciously and be educated as individuals with digital literacy skills has made it necessary to reorganize learning environments. It is very important that teachers who educate future generations and play an active role in acquiring these skills to individuals are digitally literate individuals (Akkoyunlu & Yılmaz Soylu, 2010;Kuru, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…With the penetration of technology into all areas of life, and in particular educational institutions, the necessity for students to use technology effectively and consciously and be educated as individuals with digital literacy skills has made it necessary to reorganize learning environments. It is very important that teachers who educate future generations and play an active role in acquiring these skills to individuals are digitally literate individuals (Akkoyunlu & Yılmaz Soylu, 2010;Kuru, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In the related literature, there are some study results in which the digital literacy levels of university students are found to be 'high' (Can et al, 2020;İşioğlu & Kocakuşak, 2012;Khalid et al, 2015;Kozan, 2018;Kozan & Özek, 2019;Üstündağ et al, 2017;Ocak & Karakuş, 2019;Özoğlu, 2019;Öztürk & Budak, 2019;Svensson & Baelo, 2015); 'low' (Campbell, 2016;Coşkun et al, 2013;Cote & Milliner, 2016;Kuru, 2019;Rambousek et al, 2016) and 'moderate' (Çetin, 2016;Çukurbaşı & İşman, 2014;Tyger, 2011). There are many studies in which there is a significant difference between the digital literacy levels of students in terms of the gender variable (Çam & Kyici, 2017;Çetin, 2016;Deryakulu, 2007;Gökçearslan & Bayır, 2011;Göldağ & Kanat, 2018;Gui & Argentin, 2011;Gürtekin, 2019;Hamutoğlu et al, 2017a;Horne, 2007;Korkut & Akkoyunlu, 2008;Kozan, 2018;Markauskaite, 2005;Nasah et al, 2010;Ocak & Karakuş, 2019 ;Özden, 2018;Özerbaş & Kuralbayeva, 2018;Özoğlu, 2019;Öztürk & Budak, 2019;Sakal, 2019Sakal, ,2020Sarıkaya, 2019;Sulak, 2019;Tsai et al, 200...…”
Section: Digital Literacymentioning
confidence: 99%
“…When literature is examined, it is seen that there are studies which are aimed at determining digital literacy, digital competence and digital profiles of teachers and teacher candidates (Aksakal et al, 2021;Aksoy et al, 2021;Alarcón et al, 2020;Çukurbaşı & Kıyıcı, 2018;Esteve-Mon et al, 2020;Geçgel et al, 2020;Göksu & Koçak, 2020;Gündüz, 2021;Händel et al, 2020;Karaoğlan Yılmaz & Binay Eyuboğlu, 2018;Kormos, 2018;Kurniawati et al, 2018;Kuru, 2019;Li et al, 2019;Pischetola, 2020;Quaicoe & Pata, 2018;Singh, 2021;Yalçın, 2017;Wilson et al, 2020;Yazıcıoğlu et al, 2020). The results of some of the researches that served as a source for the research were analysed.…”
Section: Introductionmentioning
confidence: 99%